Economy of the unlost : reading Simonides of Keos with Paul Celan - Carson, Anne, 1950- (Princeton, N.J. : Princeton University Press, 1999)
The ancient Greek lyric poet Simonides of Keos was the first poet in the Western tradition to take money for poetic composition. From this starting point, Anne Carson launches an exploration, poetic in its own right, of the idea of poetic economy. She offers a reading of certain of Simonides' texts and aligns these with writings of the modern Romanian poet Paul Celan, a Jew and survivor of the Holocaust, whose "economies" of language are notorious. Asking such questions as, What is lost when words are wasted? and Who profits when words are saved? Carson reveals the two poets' striking commonal.
False sail -- Alienation -- Visibles invisibles -- Epitaphs -- Negation -- All candled things.
Includes bibliographical references (pages 135-143) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Simonides, -- approximately 556 B.C.-467 B.C. -- Criticism and interpretation; Celan, Paul -- Criticism and interpretation; Celan, Paul -- Criticism and interpretation; Simonides, -- approximately 556-467 B.C. -- Criticism and interpretation; Celan, Paul; Simonides, -- approximately 556 B.C.-467 B.C.; Comparative literature -- Greek and German; Comparative literature -- German and Greek; Economics in literature; Aesthetics; Économie politique dans la littérature.; LITERARY CRITICISM -- Ancient & Classical; POETRY -- Ancient & Classical; Aesthetics; Comparative literature -- German and Greek; Comparative literature -- Greek and German; Economics in literature; Dichtkunst; Economische aspecten; Grieks; Duits; Criticism, interpretation, etc